Characterizations of hospitalizations of children and adolescents due to external causes in the intensive care unit (Research, Society and Development, 2022)
Introduction: External causes may have a great impact on infant mortality and morbimortality especially because such causes may be evitable. When there is the necessity of assistance at a Pediatric Intensive Care Unit (PICU), this population may evolve to clinical severity and instability, as well as adverse outcomes to the hospitalization process. Objective: Analyze hospitalizations due to external causes, correlating them with severity variables and length of hospital stay, in a PICU in Parana, Brazil. Methods: Cross-sectional study of children and adolescents under 15 years old, admitted between 2012 and 2017, diagnosed with external causes. The dependent variables included the need of vasoactive drugs, sedoanalgesia and mechanical pulmonary ventilation, diagnoses of health-care-related infection (HCRI), PICU and hospital stay length end obit. I was adopted significance level of 5%, with prevalence rate (PR) calculation and confidence interval (CI 955) through Poisson’s Regression. Results: In this period, 1122 children were admitted, being 145 victims of external causes, representing 13.1% of the admission, predominantly boys, over 6 years old with no diagnosis of chronic disease. The most frequent admissions occurred from traumas, and there was less prevalence of HRCI (RP=0.59; IC95%0.39-0.88), shorter hospitalization length in PICU (≤ 4 days) (PR=0.71; IC95% 0.56-0.91) and in hospital (≤ 11 days) (PR=0.70; IC95% 0.56-0.89), and lesser obit frequency (RP=0.33; IC95% 0.17-0.67) among these victims. Conclusion: Victims of external causes presented lesser prevalence of possible adverse outcomes in relation to the other admissions.